Economic modeling in the Nordic countries - Bergman, Lars, 1945-; Olsen, Øystein (North-Holland, 1992)
A selection of macroeconomic models used, or intended for, economic forecasting or policy analysis in the four Nordic countries (Denmark, Finland, Norway and Sweden), is presented in this volume. New features and model applications are discussed and the models used by the Ministries of Finance are evaluated, with special attention to the role of relative prices and their treatment of the supply side. In addition there is a systematic comparison of results from model simulations on the main macroeconomic models in the four Nordic countries. The papers fall naturally into two sections. In Part One the focus is on the short-to-medium term models; in Part Two the focus switches to a presentation of three models that may all be classified as applied general equilibrium (AGE) models.
Keywords: Economic forecasting -- Scandinavia -- Econometric models.; Economic forecasting -- Scandinavia -- Mathematical models.; Business & Economics -- Economic Conditions.; Economics.; Scandinavia -- Economic policy.; elektronické knihy; electronic books